The impact of teachers' motivating style and student-teacher relationships on adolescents' class participation: The indirect role of learning motivation - Fei Xu; Lizhen Wang; Jinnuo Xu (Acta Psychologica)
In today's competitive society, education's importance is widely recognized. Adolescence is a crucial stage during which individuals experience significant physical and mental growth and form positive learning attitudes. As society's future drivers, adolescents' learning and class participation are vital for personal growth and social progress. Teachers play a crucial role as knowledge transmitters and providers of psychological support. This study explores the relationships among teachers' motivating styles, student-teacher relationships, adolescents' class participation, and the indirect role of learning motivation. This study surveyed 658 students and employed quantitative methods to analyze how teachers' motivating style and student-teacher relationships influences class participation. The findings indicate that autonomy support style and student-teacher relationships positively influence class participation, whereas controlling style has a significant negative effect on class participation. Adolescents' learning motivation served as a complementary partial indirect effect pathway linking teachers' motivating styles and student-teacher relationships to classroom participation. These findings provide meaningful insights for both theoretical understanding and intervention strategies regarding the role of adolescents' class participation.